Pengembangan Media Pembelajaran Ekonomi Berbasis Komputer Model Drills untuk Siswa Kelas X SMA Islam Bina Insan - Sapka Mawarzani; Refreandi Haeri (Universitas Hamzanwadi, 2020)
Media is anything that can be used to transmit messages from sender to receiver so that it can stimulate thoughts, feelings, attention, and student interests in such a way that the learning process occurs, media in education is used to improve the quality of learning, one of which is based learning media. computer. It is the duty and responsibility of the teacher in utilizing learning media that is in accordance with the needs and interests of student learning, and one of the media that is in accordance with student learning interests, namely computer-based learning media drills model. The objectives of this research and development are: 1) to produce a Drills model of computer-based economic learning media which will be used for the following years in class X students of Bina Insan Islamic Senior High School 2) to determine the feasibility of computer-based economic learning media developed according to the assessment of media experts and experts material, 3) knowing the responses of expert validators and students to the Drills model of computer-based economics teaching materials that have been developed, and 4) knowing the effectiveness of the developed drills model of computer-based economic learning media. This type of research is development research with the Borg and Gall model which has been modified into eight development steps. Development steps include: 1) potentials and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product testing, 7) product revision, and 8) final product. Data collection was carried out by means of questionnaires and tests. The target output of this research is publication in accredited national journals, another output can be a computer-based learning media product model of drills.The results showed that, 1). There is a product in the form of a computer-based economic learning media with the Drills model for Bina Insan Islamic Senior High School. 2). This Drills model of computer-based economic learning media is feasible to use, it can be seen from the validation results of economic material experts of 89.09% (feasible), for media experts it is 92.30% (feasible). 3). The teacher and student responses showed a positive response seen from the results of field trials, namely the results of the teacher's questionnaire response of 100% and student responses of 89.6%. 4). For the results of student learning activities of 3.7, thus the Driils Model of computer-based economic learning media is effectively used